THE MAN” BY TAYLOR SWIFT: A VISUAL AND LYRICAL CRITIQUE OF GENDER INEQUALITY - WIJAYA, DEBI PANGESTUTI (Serat: Journal of Literary & Cultural Studies, 2025)
Taylor Swift’s song and music video “The Man” explicitly highlight gender-based double standards, offering a bold critique of systemic inequality through visual and lyrical storytelling. The work presents a clear commentary on how women are perceived and treated differently from men in professional, social, and cultural settings. “The Man” by Taylor Swift offers an image through which to look at and comprehend these gaps through her lyrics and music video. The purpose of this study is to identify and analyse gender inequality issues in the lyrics and music video to “The Man.” This study looks at the lyrics and music video using a qualitative content analysis approach to find basic themes and messages about gender inequality through the story and symbolism of the song in an effort to reveal both explicit and implicit messages on gender inequality. By analysing the lyrics and music video, this study uncovers insight into current gender inequality and the double standards in modern times. Additionally, “The Man” also shows the continuous fight for gender equality and female empowerment.